The role of subchondral bone plate porosity during the development of osteoarthritis in guinea pigs - Baharuddin, Aina; Akman, Akma Azmiera; Tarlton, John F.; Brown, Kate Robson; Sharif, Mohammed; Zamli, Zaitunnatakhin (2016)
Osteoarthritis (OA) is a degenerative joint diseases characterised by pain, immobility, cartilage degradation and subchondral bone changes that progressed as a function of age. Despite the extensive studies in human and animal models of OA, the roles of subchondral bone plate (Sbp) porosity during development of OA have yet to be determined. Hence, the present study aims to determine the spatial and temporal changes of subchondral bone plate and cartilage in spontaneous animal models of OA: Dunkin Hartley (DH) and Bristol Strain 2 (BS2) guinea pigs. Micro-computed Tomography Analyser (CTAn) software was used to determine the Sbp thickness, porosity and bone mineral density (BMD) in DH and BS2 tibia at 10, 16, 24 and 30 weeks of age. The cartilage changes were determined by OARSI microscopic scoring system. The data were then compared between strains, sides and time points. The results showed that the Sbp and cartilage changes were more prominent in the medial side of the tibia (vs. lateral side), and in the DH (vs. BS2). Unlike the control regions, the medial side of DH Sbp was initially thinner (p =0.027) and less number of open porosity (p=0.003). However, by 30 weeks of age, the Sbp had an increase of thickness and open porosity, but a decrease of closed porosity. A significant correlation was only observed between the Sbp open porosity and BMD (r=0.284, p ≤ 0.05), suggesting that these spatial and temporal changes may indicate the malalignment of the knee joint, which subsequently may lead to active Sbp remodelling.